Standard of distinguished scientific research - Bousbaa, Fouad (Journal of Human Sciences, 2021)
The methodology is linked to the legal sciences and with its different branches, it aims to give the student the scientific method to deal with different subjects and provide him with tools to obtain information to accomplish various scientific activities, train him to understand and accelerate perception. Because of the elements of methodology, thought and scientific research that is considered one of the methods researchers in the development of science to achieve knowledge by adding new scientific value. The objective of Scientific Research is to reveal and confirm the existence of a scientific fact or to add new facts, since the methodology is the path that the researcher should take since the intention of starting scientific research and determining the subject of his research in addition to all the guidelines, means and techniques helping the researcher in his research.